Target Detection in a Highway Scenario with Extended V2V Channel Model - Khan, Aamir Ullah; Haider Shah, Syed Najaf; Schneider, Christian; Robert, Joerg (IEEE Wireless Communications and Networking Conference, WCNC, 2024)
Integrated Communication and Sensing (ICAS) rep-resents an exciting new research field that combines communication and radar sensing functionalities under a single platform. This convergence leverages the similarities in signal processing, spectrum utilization, and system design between the two functionalities. The main difference between sensing and communication is their ability to use different segments of the propagation channel because of their distinct system requirements. In Vehicular Ad-hoc Networks (VANETs), existing channel models are designed purely for V2V (Vehicle to Vehicle) or V2X (Vehicle to Anything) communications. With the sole purpose of communication, such channel models lack the capability of radar sensing. ICAS demands simultaneous communication and target sensing. Therefore, in this paper, we extended a communication-based V2V channel model to integrate target detection, thus realizing an ICAS system. We considered a two-way highway scenario in the presence of Diffuse (DI) scattering components. DI components can result in high-power reflections for small distances. Therefore, the integration of the DI components is vital for the development of accurate target detection algorithms. In our simulations, we showed that the extended ICAS channel model can detect Dynamic Targets (DT) alongside its communication functionality. In addition, we also demonstrate the impact of a strong Direct Link (DL) between the Transmitter (Tx) and Receiver (Rx) on target detection.
CRIS-Team Scopus Importer:2024-11-19
Keywords: deterministic channel models; ICAS; ray-tracing; Spatial channel models; stochastic channel models